Mengkuang - Natashah Md. Nor; Rusli Harun; Fauzi Daud (Malaysia : UAS Communications (M), 1997)
Describe on the art of weaving in Perlis especially on mate weaving that made of mengkuang shrub
Copy available in DVD format
Executive producer, Najib Shafion, Zabidi Sanip ; script, Ahmad Muhaimin
Narrator: Reemy Abdul Rahman
VHS format
Keywords: Weaving; Basket making; Rugs